全新世北大西洋冷事件:年代学和气候影响 - 王绍武 (第四纪研究, 2009)
回顾了全新世北大西洋冷事件的研究,重点分析年代学和气候影响.首先,综合北大西洋8个深海沉积序列13种不同指标反映的冷事件,证明Bond等(1997)的研究是有代表性的.全新世的9次冷事件,由近及远编号0～8,出现于0.4 kaB.P.,1.4 kaB.P.,2.8 kaB.P.,4.2 kaB.P.,5.9 kaB.P.,8.1 kaB.P.,9.4 kaB.P.,10.3kaB.P.和11.1 kaB.P.其次,从早全新世到晚全新世逐一地综述了9次冷事件出现时间及气候影响.发现与冷事件对应的气候异常,主要表现为北半球高纬寒冷、低纬亚非季风区干旱.也有迹象表明出现冷事件时西-中欧及北美北部气候湿润.最后分析了冷事件的成因.早全新世冷事件可能与融冰淡水脉冲有关,中-晚全新世太阳活动减弱可能是冷事件发生主要原因,但不排除有气候系统内部振荡的影响. Studies on Holocene cold events in the North Atlantic were reviewed. The chronology and climatic impact of these cold events were examined. Nine cold events weree identified according to 13 proxy indices of oceanic sediments at 8 sites of the North Atlantic. The sediments at the 8 site, numbered 0,1,2, to 8, respectively, were dated around 0.4kaB. P., 1.4kaB. P., 2.8kaB. P., 4.2kaB. P., 5.9kaB. P., 8.1 kaB. P., 9.4kaB. P., 10.3kaB. P., and 11.1kaB. P. By Bond et al. (1997). Chronology and climatic impact were outlined from event to event. Climatic patterns related to the cold events are characterized by cooling in high latitudes and drying in lower latitudes,especially in Africa-Asian monsoon regions. There are some indications which show that climate was wet in the west-central part of Europe and in the northern part of North America when a cold event occurred in the North Atlantic. The factors were examined that might be responsible for the occurrence of cold events in the North Atlantic. It should be emphasized that the pulse of glacier melt water to be the first candidate to form cold events in Early Holocene,while the solar activity-irradiance minima to be the main cause to form cold events in mid-late Holocene. Oscillations within the climate system would possibly intensify the cold event if the condition was proper. 财政部/科技部公益类行业专项项目 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 0 6 1146-1153 29